2003
DOI: 10.1159/000068784
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dementia in China

Abstract: To obtain prevalence estimates of dementia in China, an analysis of 17 studies published in Chinese from 1990–1999 was carried out. The prevalence rates for the population aged 60 years and older were 1.26% for Alzheimer’s disease (AD) and 0.74% for vascular dementia (VD). The prevalence of AD was 2.10% in women and 0.76% in men, while the prevalence of VD was 0.71 and 0.69%, respectively. The prevalence of AD among the three educational levels in our study (illiterate, primary school and high school) were 1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…This study of Chinese populationbased subject samples over 60 years of age confirmed that dementia was a common medical condition, particularly in the elderly. The pooled prevalence of AD and VD for the Chinese population aged 60 years and older was 1.6 and 0.8%, respectively, similar to that previously reported by Liu et al [35], but lower than that reported over the last two decades in Europe [5]. We also confirmed that AD and VD are the two major subtypes of dementia in China, as the proportions of AD and VD were 54.3 and 25.5%, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study of Chinese populationbased subject samples over 60 years of age confirmed that dementia was a common medical condition, particularly in the elderly. The pooled prevalence of AD and VD for the Chinese population aged 60 years and older was 1.6 and 0.8%, respectively, similar to that previously reported by Liu et al [35], but lower than that reported over the last two decades in Europe [5]. We also confirmed that AD and VD are the two major subtypes of dementia in China, as the proportions of AD and VD were 54.3 and 25.5%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Our study also showed that the prevalence of AD was higher in women than men within the same age category, but there was no significant difference for VD. The results of several meta-analyses also showed that the prevalence of AD was higher in women than men among the senior population [35,44]. However, in the Kungsholmen Project in Sweden, there were no observed sex differences found in AD prevalence among those under the age of 85.…”
Section: Discussionmentioning
confidence: 97%
“…This study in Cotonou highlights the fact that dementia affects both men and women, but that females predominate, as shown in several other studies [6,8,32,33] . The prevalence of dementia increases with age.…”
Section: Discussionsupporting
confidence: 83%
“…These rates are lower than those reported in previous studies of domestic rural and urban areas; 10.8% in the Youngil gun of Gyeongsangbuk-Do , 9.5% in the Yonchun gun of Gyeonggi-Do ( Woo et al, 1997), 10.6% in the Sanggye-dong of Seoul (Cho et al, 1998), 13.0% in the Gwangmyung City of Gyeonggi-Do (Kwak et al, 1999), and 8.2% in Seoul (Lee et al, 2002). However, it was higher than those of the studies of foreign countries; 5-6.3% in USA (Folstein et al, 1975), 4.8% for Latino in California (Haan et al, 2003), 3.6-11.9% in Europe (O'Connor et al, 1989Rocca et al, 1990;Fratiglioni et al, 1991;Dartigues et al, 1991;Prencipe et al, 1996), 6.7% in Okinawa, Japan (Ocura et al, 1995), 3.7% in southern Taiwan (Lin et al, 1998), and about 3% in China (Liu et al, 2003).…”
Section: Prevalence Rate Of Dementiamentioning
confidence: 99%